Italian good practice recommendations on management of persons with Long-COVID - Giuliano, Marina; Tiple, Dorina; Agostoni, Piergiuseppe; Armocida, Benedetta; Biardi, Ludovico; Bonfigli, Anna Rita; Campana, Andrea; Ciardi, Maria; Di Marco, Fabiano; Floridia, Marco; Gnerre, Paola; Grassi, Tiziana; et al. (Frontiers in Public Health, 2023)
A significant number of people, following acute SARS-CoV-2 infection, report persistent symptoms or new symptoms that are sustained over time, often affecting different body systems. This condition, commonly referred to as Long-COVID, requires a complex clinical management. In Italy new health facilities specifically dedicated to the diagnosis and care of Long-COVID were implemented. However, the activity of these clinical centers is highly heterogeneous, with wide variation in the type of services provided, specialistic expertise and, ultimately, in the clinical care provided. Recommendations for a uniform management of Long-COVID were therefore needed. Professionals from different disciplines (including general practitioners, specialists in respiratory diseases, infectious diseases, internal medicine, geriatrics, cardiology, neurology, pediatrics, and odontostomatology) were invited to participate, together with a patient representative, in a multidisciplinary Panel appointed to draft Good Practices on clinical management of Long-COVID. The Panel, after extensive literature review, issued recommendations on 3 thematic areas: access to Long-COVID services, clinical evaluation, and organization of the services. The Panel highlighted the importance of providing integrated multidisciplinary care in the management of patients after SARS-CoV-2 infection, and agreed that a multidisciplinary service, one-stop clinic approach could avoid multiple referrals and reduce the number of appointments. In areas where multidisciplinary services are not available, services may be provided through integrated and coordinated primary, community, rehabilitation and mental health services. Management should be adapted according to the patient’s needs and should promptly address possible life-threatening complications. The present recommendations could provide guidance and support in standardizing the care provided to Long-COVID patients.